Gaining supervision skills in pre-registration nursing through peer teaching: An evaluative survey - Karolina Martins; Amanda Wagg; Elsa Afonso (Heliyon, 2022)
Background: It is now a requirement that all qualified nurses act as practice supervisors and support student nurses' education in practice, hence preparing third-year students for this role is a priority. This study evaluates students' experiences of peer teaching in clinical skills setting from the perspective of these students taking up the supervisory role once they graduate. Method: An evaluative survey was utilised to explore and understand student nurse participation in peer teaching. Seventeen students took part in a questionnaire containing closed and open questions. Results: This research suggests that students who engaged in peer teaching gained confidence in their own skills, through the revision of their own skills and knowledge. It also triggered reflection upon continuous professional development and inspired students to consider a future career in teaching. Conclusion: Peer teaching provides an opportunity to reinforce the students' knowledge, clinical and communication skills. It helps prepare them for the role of practice supervisor upon qualifying by building confidence and enhancing their teaching skills.